An application of ionic liquid for preparation of homogeneous collagen and alginate hydrogels for skin dressing - Iqbal, B. (Elsevier B.V., 2017)
Ionic liquid due to its green nature as well as having the ability to dissolve biopolymer, was used in the preparation of collagen and alginate hydrogels. The collagen and alginate hydrogels were prepared in different ratios of collagen and alginate, labeled CA5040, CA6030 and CA7020. The prepared hydrogels were characterized with Fourier-transform infrared spectroscopy (FTIR), Scanning electron microscope (SEM), Thermogravimetric analysis (TGA) analysis. The samples were evaluated for water uptake behavior and mechanical properties using electrodynamic fatigue testing system. The biocompatibility was assessed through hemolysis and MTT assay on rat mesenchymal stem cells (rMSC) which showed satisfactory results. The drug loading and subsequent antibacterial properties were also performed. The prepared collagen and alginate hydrogels are suggested to be used for skin dressing. © 2017